Role of biochar in anaerobic microbiome enrichment and methane production enhancement during olive mill wastewater biomethanization - Abid, Nozha; Karray, Fatma; Kallel, Imen; Slim, Mariam; Barakat, Abdellatif; Mhiri, Najla; Chamkha, Mohamed; Sayadi, Sami (Frontiers in Bioengineering and Biotechnology, 2023)
The current research work attempted to investigate, for the first time, the impact of biochar addition, during anaerobic digestion (AD) of olive mill wastewater (OMW) with different initial chemical oxygen demand (COD) loads in batch cultures (10 g/L, 15 g/L and 20 g/L). Methane yields were compared by applying one-way analysis of variance (ANOVA) followed by post hoc Tukey’s analysis. The results demonstrated that biochar addition at 5 g/L to OMW with initial COD load of 20 g/L increased methane yield by 97.8% and mitigated volatile fatty acids (VFAs) accumulation compared to the control batch. According to the results of microbial community succession revealed by Illumina amplicon sequencing, biochar supplementation significantly increased diversity of the microbial community and improved the abundance of potential genera involved in direct interspecies electron transfer (DIET) including Methanothrix and Methanosarcina. Consequently, biochar can stand for a promising alternative in terms of the recovery of metabolic activity during AD of OMW at a large scale.